The Classical 6-P of Acute Limb Ischemia - Zakhi, Adib (International Journal of Human and Health Sciences (IJHHS), 2023)
Acute limb ischemia (ALI) is a surgical emergency and often threatens limb viability. This is a case of a 45-year-old patient who presented with the classical six Ps of ALI. A 45-year-old lady with underlying hypertension and heart failure presented with acute right leg pain arriving by ambulance at the Emergency Department within 4 hours of the symptom. The patient was clinically obese and seemed very uncomfortable as evidenced by her writhing in pain. She was borderline tachycardic and hypertensive. The cardiopulmonary and abdominal examinations were unremarkable. On extremity examination, she was unable to move her right leg starting from the knee caudally. The leg appeared mottling and cold. On vascular examination, there was no abdominal or femoral bruit but there was a diminished pulsation of the right femoral, dorsalis-pedis and posterior-tibialis arteries as confirmed by Doppler compared to the contralateral side. On the neurological examination, the sensation was absent and no pain upon the passive stretch. Ankle-Brachial-Systolic Index (ABSI) was 0.7. As evidenced by pain, pallor, pulselessness, poikilothermia, paralysis, and paresthesia, clinical diagnosis of acute right leg ischemia was established with most likely vascular occlusion proximal to the left femoral artery. The vascular team was urgently referred. Electrocardiogram showed sinus tachycardia. Bedside ultrasound revealed normal aortic root size and neither aortic dissection nor aneurysm. 2-point compression tests were fully compressible and X-ray films showed no fracture. Creatinine Kinase was 65 units/litre whereas other blood parameters were unremarkable. She was then classified as Rutherford IIB and underwent a right femoral thromboembolectomy. The presentation of ALI requires rapid diagnosis and appropriate management as it is time-sensitive and limb-threatening. Emergency physicians should be aware of advances in endovascular therapies as a recommended option for the treatment of ALI. International Journal of Human and Health Sciences Supplementary Issue: 2023 Page: S23